Morphological and Biomass Responses of Oil Palm Varieties to Salinity in Early Nursery - Eka Bobby Febrianto; Rosmayati Rosmayati; Sri Murti Tarigan; Wagino Wagino (Agrosains : Jurnal Penelitian Agronomi, 2026)
Salinity is an important constraint in oil palm nurseries because it may limit seedling growth and reduce the potential use of marginal land or growing media. This study evaluated the morphological and biomass responses of five oil palm varieties to salinity in early nursery and identified practical variables for early selection under saline conditions. The experiment was conducted in a greenhouse using a factorial randomized complete block design with five varieties, three salinity levels, and three replications. The observed variables were stem diameter, number of leaves, canopy length, root length, shoot fresh weight, root fresh weight, shoot dry weight, root dry weight, and root-shoot ratio. Data were analyzed using analysis of variance followed by Duncan’s Multiple Range Test at the 5% level. Varietal effects were significant for all observed variables, whereas salinity as a single factor was not significant within the tested range. However, the interaction between variety and salinity significantly affected most variables, indicating that seedling responses to salinity depended on varietal background. DxP Socfindo Yangambi and DxP Socfindo Lame showed the best performance under saline conditions, particularly at 6-7 mmhos cm-1, as reflected in canopy growth, root elongation, and biomass accumulation. In contrast, DxP Simalungun showed the weakest response across most variables. Canopy length, root length, shoot dry weight, and root dry weight were the most informative variables for early selection of oil palm seedlings under saline conditions.